The Influence of Human Resource Management, Organizational Commitment, and Work Discipline on Employee Performance Mediated by Job Satisfaction - Basir, Abdul (Universitas Dharma Wacana, 2025)
The purpose of this study is to examine how work discipline, organizational commitment, and human resource management affect team member performance and how job satisfaction mediates these effects. This study used both a quantitative method and a causally associative approach. The study's population consisted of team members employed in Indonesia's state-owned banking industry. Purposive sampling was used to choose the 78 employees that made up the research sample. Data is gathered through survey methods, and employees are given questionnaires to fill out. Partial least squares structural equation modeling (PLS-SEM) is used in SmartPLS data analysis. The results of the study indicate that work satisfaction and human resource management significantly affect team member performance. On the other hand, team members' performance was not significantly impacted by organizational commitment or work discipline. Job satisfaction can operate as a stronger mediator between the effects of organizational commitment and human resource management on team member performance. It does not, however, act as a mediator in the link between team members' performance and work discipline. By including current issues unique to the banking industry, this study adds to the conceptual foundation of team members' performance. Financial institutions can benefit from the study's insightful recommendations, which emphasize the significance of creating all-encompassing plans that combine team member welfare with corporate goals.